Hepatic metastasis of differentiated thyroid carcinoma - Kraft, Otakar (Nuclear medicine review. Central & Eastern Europe, 2005)
BACKGROUND: Differentiated thyroid cancers (DTC) often form metastases in neck lymph nodes, lungs and bones. Other metastases--to the brain, kidneys, skin and liver are rare. Liver metastases of DTC occur in the terminal phase of the disease and predominantly do not accumulate radioiodine. Functional (accumulating radioiodine) metastases are very rare. MATERIAL AND METHODS: In an 85 year old patient with DTC of the follicular type after removal of the thyroid and lymph nodes metastases on the neck and after the elimination of thyroid remnants by radioiodine, a functional metastasis in the liver was detected by combination of whole-body scintigraphy following administration of 131I and liver scintigraphy by using 99mTc-colloid, supplemented by bone scintigraphy after administration of 99mTc-MDP. At first, the high thyroglobulin serum level was falsely negative after repeated radioiodine treatment. The patient was treated for this hepatic accumulating metastasis eight times by 59.2 GBq total dose of radioiodine. Radioiodine treatments were repeated for 7 years, the patient died at the age of 92 years. CONCLUSIONS: It is necessary to distinguish between diffuse and focal radioiodine accumulation in a liver. Only a focal accumulation is characteristic for functional liver metastasis in which thyroxin synthesis is preserved. The correspondence of focal accumulation of radioiodine on whole-body scintigraphy with "cold" area on liver scintigraphy is specific for diagnosis of this metastasis. At the same time, it confirms the fact that radioiodine therapy can be both promising and successful, as we can see in the case of our patient.
Keywords: senioři; metastázy nádorů; Liver; thyroxin; Liver Neoplasms; játra; Cell Differentiation; senioři nad 80 let; nádory jater; výsledek terapie; lymfatické metastázy; Tomography, Emission-Computed, Single-Photon; nádory štítné žlázy; radioizotopy jodu; Carcinoma; Lymphatic Metastasis; Aged, 80 and over; Neoplasm Metastasis; Radionuclide Imaging; Thyroid Neoplasms; Humans; radioisotopová scintigrafie; buněčná diferenciace; Thyroxine; Aged; jednofotonová emisní výpočetní tomografie; Treatment Outcome; Iodine Radioisotopes; lidé; karcinom